2017
DOI: 10.1111/gcbb.12424
|View full text |Cite
|
Sign up to set email alerts
|

Annual balances and extended seasonal modelling of carbon fluxes from a temperate fen cropped to festulolium and tall fescue under two‐cut and three‐cut harvesting regimes

Abstract: Annual balances and extended seasonal modelling of carbon fluxes from a temperate fen cropped to festulolium and tall fescue under two-cut and three-cut harvesting regimes AbstractThis study reports the annual carbon balance of a drained riparian fen under two-cut or three-cut managements of festulolium and tall fescue. CO 2 fluxes measured with closed chambers were partitioned into gross primary production (GPP) and ecosystem respiration (ER) for modelling according to environmental factors (light and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The field mainly comprises organic soil areas and small zones with mineral soils (coarse sand). This site is considered as a riparian fen peatland [34] where vascular plants such as reeds and sedges dominate [12]. As will be discussed later, and similar to Walter et al [12] (2015), its specific configuration, underlain by sandy soils characterized by low electrical conductivity, ensured a contrast with the peat layers, which generally present higher electrical conductivity.…”
Section: Study Areamentioning
confidence: 81%
“…The field mainly comprises organic soil areas and small zones with mineral soils (coarse sand). This site is considered as a riparian fen peatland [34] where vascular plants such as reeds and sedges dominate [12]. As will be discussed later, and similar to Walter et al [12] (2015), its specific configuration, underlain by sandy soils characterized by low electrical conductivity, ensured a contrast with the peat layers, which generally present higher electrical conductivity.…”
Section: Study Areamentioning
confidence: 81%
“…These guidelines are needed to guide the user of the HMR package to analyse the recorded data consistently to achieve the best possible flux calculations. Differences between sampling systems may be inherent to the sampling methodology, chamber design (probably a minor factor in our study because the chamber dimensions were relatively similar for both systems), length of deployment (Kandel et al, 2017) and the number of data points (Hüppi et al, 2018;Parkin et al, 2012). Both older and more recent studies of N 2 O emissions from soil have used linear regression as the only way to calculate N 2 O fluxes (Christensen et al, 2021;Guo et al, 2021;Pugesgaard et al, 2017;Smith & Dobbie, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of heavy metals resulted in more obvious inhibitory effects. Some studies have found that proper cutting methods stimulate root activity and promote the growth of aboveground plants (Kandel, Elsgaard, & Lærke, 2017). However, our results indicated that the cutting method reduced the biomass of tall fescue under Cd stress because the increased cutting treatment promoted the absorption of Cd by the plant, which caused the high concentration of Cd in the plant to affect the physiological activity of plants (Dias et al., 2013).…”
Section: Discussionmentioning
confidence: 99%